Algunas características aspectuales de los verbos de percepción física en español: ver frente a mirar - Devís Márquez, P. Pablo (Verbum – Analecta Neolatina, 2010)
The aim of this paper is to comment on some particular aspectual characteristics of the verbs of sensorial perception in Present-Day Spanish and the differences of syntactic behaviour that these characteristics suppose. The interrelation between aspectual information and syntax, just as it happens with other types of verbs, seems evident. In the particular case of the pair ver-mirar, we propose that aspectual characteristics do not only entail diversity of syntactic structures but also lexical differences.